PARENTAL PARTICIPATION IN FREE DAY SECONDARY EDUCATION AND STUDENT RETENTION: A CASE OF MIGORI COUNTY, KENYA - Achieng, Madeleine Sophie Barat; Harriet Njui (IJRDO- Journal of Educational Research, 2020)
Research shows that parental participation in the educational experiences of their children increases student achievement and strengthens school programmes. Majority of research done have however concentrated on lower and upper primary schools with little being known about parental participation at secondary school level. The study was anchored on systems theory and sought to add to literature related to parental participation at secondary level. The study examined the experiences of school principals, class teachers, students and parents on parental participation in public day schools and student retention in Migori County. The study targeted 215 public day secondary schools. The actual sample size was made up of 19 schools, 19 principals, 76 class teachers, 228 students and 31 parents. The study adopted a convergent parallel mixed method design using cross sectional survey for the quantitative method and a case design for the qualitative method. The researcher collected data using questionnaires, interview guide and focus group discussions. Quantitative data were analysed using descriptive statistics generated from Statistical Package for Social Sciences (SPSS) version 21 while qualitative data were analysed thematically and reported in narrative form. The findings revealed that most parents provide material support, financial support and services as contribution towards school expenses. The study recommends that the government through the Ministry of Education Science and Technology should formulate policies aimed at involving parents actively in planning, decision making and financing of day secondary schools. Principals need to encourage parents’ participation in free day secondary education programme. They also need to maintain good relations and information flow with parents, local community, sponsors and the local council.